Urban sustainability assessment for vernacular and traditional built environments - Fahad Matar; Falli Palaiologou; Simon Richards (Journal of Urban Management, 2023)
Despite the growing literature on sustainability assessment in the urban context, the resulting approaches and methods utilise several differing theoretical frameworks and lack a unifying vision and modus operandi. Innumerable tools and instruments have been developed for particular purposes and rather narrow goals. Curiously, these tools and instruments remain unable to trace and assess sustainability in vernacular forms and traditional built environments, even though environments such as these demonstrably possess sustainable principles beside their aesthetic values and spatial qualities. This paper reviews the theoretical background underpinning the current sustainability assessment methods in the urban context to identify their general limitations and their specific applicability to vernacular and traditional built environments. Also, this paper discusses some of the cultural and spatial qualities of traditional built form to identify its embedded sustainable strategies and practices. The paper concludes with an outline conceptual framework intended to develop general sustainability principles for traditional built forms in response to their natural and cultural contexts. A literature review of the concepts of sustainability assessment in the urban context and embedded sustainable principles in vernacular and traditional built form is followed by a thematic analysis of its limitations, which feeds into this conceptualisation of a new, principle-based framework. A total of 10 principles of sustainability are proposed to assess sustainability in traditional built environments, taking into account the variation of locality and site-specific context.
Keywords: 710; Sustainability Assessment; Traditional built environment; Urban sustainability; Vernacular sustainability